Kehamilan Gemeli dan Ketuban Pecah Dini sebagai Risiko Kejadian Partus Prematurus Iminens - Dewa Ayu Mirah Jayantini; Sri Rahayu; I Gusti Agung Ayu Novya Dewi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Infant Mortality Rate (IMR) is a key indicator of healthcare success. This research aimed to examine the relationship between twin pregnancy and premature rupture of membranes (PROM) with the incidence of threatened preterm labor at Bali Royal General Hospital in 2023. This research is a correlational analytic study with a case-control design. The study was conducted from March to April 2023 using non-probability purposive sampling. The sample size consisted of 250 data points. Data collection involved gathering diagnoses of mothers, twin pregnancies, PROM, and threatened preterm labor. The relationship between twin pregnancy and PROM with the incidence of threatened preterm labor was analyzed using the chi-square test. The results showed that the majority of mothers with twin pregnancies experienced threatened preterm labor, amounting to 19 cases (7.6%). Most mothers with PROM also experienced threatened preterm labor, totaling 35 cases (14%). The conclusion was that gemeli pregnancies had almost 4 times the risk of developing threatened preterm labour. Premature rupture of membranes had almost 3 times the risk of developing threatened preterm labour. Bali Royal Hospital accelerate socialization for pregnant women to prevent premature rupture of membranes and premature events. Socialization can be provided by providing information through social media, putting up posters in polyclinics and holding classes for pregnant women.